2019
DOI: 10.1007/s12028-019-00711-w
|View full text |Cite
|
Sign up to set email alerts
|

Automated False Alarm Reduction in a Real-Life Intensive Care Setting Using Motion Detection

Abstract: BACKGROUND: Contemporary monitoring systems are sensitive to motion artifacts and cause an excess of false alarms. This results in alarm fatigue and hazardous alarm desensitization. To reduce the number of false alarms, we developed and validated a novel algorithm to classify alarms, based on automatic motion detection in videos. METHODS: We considered alarms generated by the following continuously measured parameters: arterial oxygen saturation, systolic blood pressure, mean blood pressure, heart rate, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Furthermore, the absence of direct contact with the skin allows for the monitoring of pre-term infants and other patients who suffer from skin irritations due to prolonged use of electrodes [7]. Another advantage of using cameras is the direct recognition of motion artifacts that reduce the vital sign quality and trigger false alarms [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the absence of direct contact with the skin allows for the monitoring of pre-term infants and other patients who suffer from skin irritations due to prolonged use of electrodes [7]. Another advantage of using cameras is the direct recognition of motion artifacts that reduce the vital sign quality and trigger false alarms [8].…”
Section: Introductionmentioning
confidence: 99%
“…This need to reduce clinically irrelevant alarms should be addressed in collaboration with key stakeholders (e.g., patients and engineers) and health services, taking advantage of the development of technology with better algorithms that reduce false alarms (Bollepalli et al, 2021; Hyland et al, 2020; Ruppel, De Vaux, et al, 2018; Wilken et al, 2019). In addition, the devices must be useful, adjusting the sensitivity and specificity of the alarms, and their operation must be easy to learn (Fernandes et al, 2020; Muroi et al, 2020). Nurse managers must acquire modern devices and facilitate the training and expertise of nurses in the use of those devices.…”
Section: Discussionmentioning
confidence: 99%
“…The monitor should detect all clinically relevant episodes and raise as little false positive alarms as possible such that alarm fatigue in health care staff can be prevented. 31 , 32 One possible way to reduce false alarms would be to incorporate additional sensor modalities, which, however, until now are still a matter of ongoing research as shown by Muroi et al 33 Another attempt would be to improve the primary detection of the signal of interest by reducing noise and artifacts at the sensor side, as we aimed to test with the acquisition of multichannel esophageal signals. The proposed NEO method captures changes of RR instead of indirect measures as bradycardia or desaturation.…”
Section: Discussionmentioning
confidence: 99%